Assessing genotoxicity of diuron on Drosophila melanogaster by the wing-spot test and the wing imaginal disk comet assay. (May 2017) - Peraza-Vega, Ricardo I; Castañeda-Sortibrán, América N; Valverde, Mahara; Rojas, Emilio; Rodríguez-Arnaiz, Rosario
The aim of this study was to evaluate the genotoxicity of the herbicide diuron in the wing-spot test and a novel wing imaginal disk comet assay in Drosophila melanogaster . The wing-spot test was performed with standard (ST) and high-bioactivation (HB) crosses after providing chronic 48 h treatment to third instar larvae. A positive dose–response effect was observed in both crosses, but statistically reduced spot frequencies were registered for the HB cross compared with the ST. This latter finding suggests that metabolism differences play an important role in the genotoxic effect of diuron. To verify diuron's ability to produce DNA damage, a wing imaginal disk comet assay was performed after providing 24 h diuron treatment to ST and HB third instar larvae. DNA damage induced by the herbicide had a significantly positive dose–response effect even at very low concentrations in both strains. However, as noted for the wing-spot test, a significant difference between strains was not observed that could be related to the duration of exposure between both assays. A positive correlation between the comet assay and the wing-spot test was found with regard to diuron genotoxicity.